International legal co-operation in combating economic crime - Пасечник, Олена Владиславівна; Пасечник, О. В.; Pasechnyk, Olena V.; Федорова, Тетяна Сергіївна; Федорова, Т. С.; Fedorova, Tetiana S.; Бірюков, Руслан Миколайович; Бірюков, Р. М.; Biriukov, Ruslan M. (Riga: Baltija Publishing, 2025)
The subject of the present study is the conceptual, theoretical and methodological research of international legal co-operation in combatting economic crimes on the international, European and state level. Methodology. The research employs a range of general scientific methods, with hermeneutic methods being utilised for the development of the research's conceptual construct and the establishment of the meaning of the terms employed. The analysis and synthesis methods were employed to establish the qualitative parameters of international police co-operation in the prevention and combatting of economic crimes, as well as to determine the methodological principles on which such co-operation is based. The comparative method was used to establish the similarities and differences between legal acts on international, regional and domestic levels. The objective of the present article is twofold: firstly, to provide a comprehensive overview of the various approaches employed in the analysis of international co-operation in the prevention and combatting of economic crime; and secondly, to establish a contemporary theoretical basis for research into the modalities of international co-operation in the aforementioned field. The findings of the study have demonstrated that effective international co-operation of States and their law enforcement authorities in combatting and preventing economic crimes is only possible upon condition of the development of the corresponding legal and institutional framework. Such a framework is to be developed at the international, regional and global levels, which are to be harmonised to achieve a common goal of preventing economic crimes. Conclusion. It has been determined that the establishment of an effective international co-operation mechanism to prevent and combat economic crime is contingent upon the presence of a suitable legal and institutional framework. This framework must be developed through systematic efforts at both domestic and international levels. It is noteworthy that a significant number of international agreements aimed at preventing and combatting various forms of crime, including economic crime, have been concluded during the late XX and early XXI centuries. In a similar vein, the European Union has developed a considerable body of legislation and practice on the matter, with relevant activities being institutionalised by the creation and empowerment of international bodies such as Interpol and Europol. In addition, States have prioritised international efforts in combatting economic crime, as evidenced by the establishment of systems of laws and bylaws directed at the elimination of international economic criminal activities, a notable example of which is Ukraine. It is anticipated that this issue will receive greater attention in the future, including through the promotion of relevant international agreements from the interdepartmental to the interstate level.
Pasechnyk O. International legal co-operation in combating economic crime / O. Pasechnyk, T. Fedorovа, R. Biriukov // Baltic Journal of Economic Studies. – Riga: Baltija Publishing, 2025. – 11(1). - Р. 174-180. URL: https://doi.org/10.30525/2256-0742/2025-11-1-174-180
Keywords: international co-operation; combatting crime; Interpol; Europol; National Police; economic crime; crime prevention